THE MAKING OF ENGLISH TABLOID OF BUSINESS ENGLISH STUDY PROGRAM - Rizka Nofianti; Rionaldi Rionaldi (INOVISH JOURNAL, 2016)
Abstract : the role of mass media is crucial today. It is used to introduce, inform, and also to promote products, services, and also entertain people. Business English Study Program is one of study programs in Bengkalis which is still limited in media use. As a result, a little information that public knows about it. Therefore, the use of mass media in English that can be read by larger target audience to introduce, inform, and promote it, its achievement and students activities is crucially needed. In this study, tabloid was chosen as media to fulfill those functions for English department. The name of the tabloid designedÂ  is â€œThe Bestâ€ (Business English Study Program Tabloid). It contains Business English Study Program profile, student and alumniâ€™s Profile, Studentsâ€™ Activity, Business Info, and Study Tips. It was created by using CorelDraw Graphic Suit X5.Â  This tabloid is expected to be a media of promotion for Business English Study Program and be a creativity media for students. Through this tabloid, it is expected that public will better know Business English Study Program Â Keywords: English, Media, Tabloid